Science Learning Based on Local Wisdom: Analysis of Multimedia use Needs Using Canva in Class V Elementary School - Astuti, Yeni Tri; Zulkardi, Zulkardi; Wiyono, Ketang (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
This research was conducted to determine students' responses to the use of learning media. This research is a qualitative research using descriptive qualitative methods. The data analysis technique used is descriptive analysis with data reduction, data presentation, conclusion drawing and verification. Data collection in this study used questionnaires with qualitative data types and distributed using google forms so that respondents could fill out questionnaires online. The results of this study showed that 78.1% of students stated that they really need interactive multimedia learning by presenting interesting elements of images, audio and video. One of the applications that supports this is the Canva application. So that it can be argued that this research can be a benchmark for teachers regarding the development of interactive science multimedia based on local wisdom can be made as attractive as possible and according to the needs of students through various applications or supporting software such as Canva